Studi Literatur Sistem Matrilineal Dalam Kehidupan Sosial-Budaya Masyarakat Dan Minangkabau Dan Dampaknya Pada Kesehatan Masyarakat Berdasarkan Program Pertukaran Mahasiswa Merdeka (PMM) Angkatan 4 Tahun 2024/2025 - Lutfhi, Safira Hanif Hisanah Nabilah; Endartiwi, Sri Sularsih (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The matrilineal kinship system applied by the Minangkabau people is a unique cultural heritage and has an important role in shaping the social structure, cultural identity, and social and mental health of the community. This system is inherited from generation to generation through the maternal line and acts as a mechanism for preserving customs and strong social support in the midst of the dynamics of social change and modernization. This study aims to examine in depth the application of the matrilineal system in the socio-cultural life of the Minangkabau people, and its impact on the social and mental health of the Minangkabau people. The approach used is a qualitative literature study with descriptive analysis, through a systematic review of various written sources such as journals, books, official reports, and cultural documents during the research period. The data were analyzed qualitatively and interpretively to understand the social, cultural, and public health significance of the matrilineal system. The results of the study show that the matrilineal system functions not only as a pattern of inheritance and social structure, but also as a mechanism for preserving cultural identity and strong social support. Rumah gadang as a symbol of women's power and a center of traditional activities serves as a concrete representation of the sustainability of this system. The system also has a positive impact on social cohesion, self-confidence, and collective emotional support in society, which is able to adapt to the challenges of modernization. The matrilineal system in Minangkabau is a dynamic and relevant cultural heritage. The sustainability of this system is highly dependent on the collective support of the community and the process of cultural innovation in a sustainable manner in order to be able to face the changing times and strengthen the social, mental, and cultural health of the community.